The impact of architectural conservation policies on the continuance of heritage buildings - Study of conservation in Sulaymaniyah governorate - Muhealddin, Banaz N; Ali, Alan Faraydoon (Sulaimani Journal for Engineering Sciences, 2019)
The issue of conservation of heritage occupies an advanced place in the context of issues of general concern to the nations of the world because it is a clear indicator of the progress of civilizations, from which subsequent generations derive their culture and their architectural identity. This paper is important in terms of philosophical, cultural, economic, and educational and sustainability aspects. The main problem in the research is the deterioration of the architectural character of the Kurdish heritage in Sulaymaniyah, especially in recent decades. The objective of the research is to evaluate and find the best solutions to the policy of preserving valuable heritage buildings and improving their ability to preserve the architectural identity of the city. The research focuses on the study of the efficiency of the architectural conservation of the old heritage buildings that underwent the process of conservation and rehabilitation, the failure of the architectural conservation and neglect policies by the authorities has resulted in the removal of the architectural values and the loss of the architectural identity of the city, which led to deterioration and distortion of the architectural character of the Kurdish heritage. The research takes an analytical approach and historical survey to contribute the prevention, deformation, and degradation of heritage buildings. The selected heritage buildings are examples of the restored architectural heritage in Sulaymaniyah Governorate. The research was based on analysis of old documents, photographs, detailed indicators of heritage buildings and surveying of buildings with surrounding areas, as well as the creation of a table to evaluate the conservation policy and analyze the impact of preserving the architectural characteristics of these buildings. The research concludes with a set of recommendations that can help improve the efficiency of architectural conservation and preserve the original heritage elements of the Kurdish community and increase community awareness regarding the importance of preserving this valuable heritage that left from ancestors to remain etched in generations’ memories. The research was able to reach to the results through the analysis of the main and secondary indicators, which are considered as tools of evaluating the conservation process in Sulaymaniyah or anywhere in the world, for protecting the architectural identity and its original characteristic.
Keywords: conservation; architectural identity; documentation; deterioration; restoration; rehabilitation